The impact of human resources practices on consumers’ investment intentions - Ferreira, Aristides I. (2018)
Purpose Research has shown that corporate policies affect customers’ decisions. The purpose of this paper is to focus on the influence of human resources (HR) practices on investment intentions in the financial sector. Design/methodology/approach Data were obtained from 548 managers and management students. Participants were presented real news regarding two banks with contrasting HR practices. Subsequently, they had to choose – from a given virtual amount – their investment allocations. Findings Results primarily showed that participants decided to invest more money in the bank which was more profitable to them, regardless of that bank’s HR practice. But, most importantly, when the news was specifically addressed to the in-group (managers), participants decided to invest more money in the bank with the HR practice by which they identified more, although being less profitable to them. Originality/value The findings demonstrate the urgency for organizations to manage effectively their HR practices, as they serve as a vehicle to corporate reputation, thus affecting the relationship with the stakeholders and investors’ decisions.